A Reflection of Shared Economy Practices in the Wuat Wa’i Tradition, East Manggarai, Indonesia - Putri, Stefani A M Aji; Hermawan, Marko S. (Journal of Ecohumanism, 2024)
The objective of this research is to understand the practice of the shared economy and the concept of debt within the Wuat Wa’i culture of the Waling Village community in East Manggarai, using an autoethnographic approach. Data were collected through literature studies, observations, and interviews with 21 informants. The findings show that the shared economy practice has three main characteristics: (1) interactions through social processes, such as the habit of visiting at any time, (2) money as a resource, and (3) temporary access creating the concept of debt. This practice brings three positive benefits: (1) values such as reduced financial burdens, equal educational opportunities, and improved social status, (2) independence, with community members solving educational cost issues independently, and (3) improved quality of life through enhanced human resources and community welfare. The concept of debt refers to a moral obligation to repay without a set timeframe, influenced by the time value of money and individual economic conditions. This moral debt creates concerns about social exclusion if not reciprocated, leading to negative behaviors such as borrowing to assist, especially for anak wina, issues in economic priority setting, and the culture of early coffee harvesting called kopi ijon.